Teach-talk and learn : innovative and interactive strategies and learning activities in speaking and vocabulary development - Velasco, Cecilia Q. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2016)
This book intended to make teaching on speaking easier and fun to the diverse types of students, both in the secondary and tertiary levels.
Preface iii -- Acknowledgments v -- Dedication vi -- Introductory remarks vii -- Teaching strategies 1 -- Learn vocabulary with fun 85 -- This is how we do it 171 -- References 175
Includes index.
Keywords: TEACHING